An Exploration of the Meaning of Gawai Dayak in Sintang, West Kalimantan: An Intergenerational Perspective - Farida, Kristianti; Setiawan, Jefri (Universitas Negeri Surabaya, 2025)
Background: The Gawai Dayak tradition represents a cultural practice encompassing a range of spiritual, social, and symbolic values passed down through generations in Dayak society. However, due to the impact of modernity, the meaning and significance of Gawai Dayak have shifted, especially among the traditional leader group and the younger generation group. Objective: This research aims to examine the intergenerational perceptions of the Gawai Dayak tradition, focusing on how these cultural values are perceived, revered, and conveyed amidst the challenges posed by modernity. Method: This study employed a qualitative design with a realism approach. Data collection was conducted through in-depth interviews with two former sub-district-level adat leaders and one Dara Gawai winner from the Sintang district. In addition, a questionnaire with open-ended questions was distributed to nine individuals aged 19-23, representing the younger generation. Thematic analysis was used to analyze the data, involving transcribing the data verbatim, categorizing it into codes, and organizing it into themes. Data credibility and authenticity were ensured using triangulation and member checking. Results: The study reveals a generational difference in the interpretation of Gawai Dayak, with the traditional leaders emphasizing its spiritual and ritual significance, while the younger generation views it more as a celebration, especially concerning alcohol consumption and rituals. Conclusion: Gawai Dayak holds different meanings across generations. Traditional leaders emphasize its spiritual aspects, while the younger generation focuses on its festive nature. These findings highlight the need for intergenerational transmission of cultural values. This research suggests the importance of preserving traditional values within communities. Keywords: Cultural identity, cultural preservation; gawai dayak; inter generational perception; modernity and tradition. Abstrak Tradisi Gawai Dayak merupakan praktik budaya yang mencakup berbagai nilai spiritual, sosial, dan simbolis yang diwariskan dari generasi ke generasi dalam masyarakat Dayak. Makna dan arti penting Gawai Dayak telah bergeser, terutama di antara kelompok pemimpin adat dan generasi muda. Tujuan: Penelitian ini bertujuan untuk mengkaji persepsi antargenerasi tentang tradisi Gawai Dayak, dengan fokus pada bagaimana nilai-nilai budaya tersebut dipersepsikan, dihormati, dan disampaikan di tengah-tengah tantangan yang ditimbulkan oleh modernitas. Metode: Penelitian ini menggunakan desain kualitatif dengan pendekatan realisme. Pengumpulan data dilakukan melalui wawancara mendalam dengan dua mantan ketua adat tingkat kecamatan dan satu pemenang Dara Gawai dari Kabupaten Sintang. Selain itu, kuesioner dengan pertanyaan terbuka dibagikan kepada sembilan orang berusia 19-23 tahun yang mewakili generasi muda. Analisis tematik digunakan untuk menganalisis data, yang melibatkan transkrip data kata demi kata, mengkategorikannya ke dalam kode-kode, dan mengorganisasikannya ke dalam tema-tema. Kredibilitas dan keaslian data dipastikan dengan menggunakan triangulasi dan pengecekan partisipan. Hasil: Penelitian ini mengungkapkan perbedaan generasi dalam interpretasi Gawai Dayak, dengan para pemimpin adat menekankan makna spiritual dan ritualnya, sementara generasi muda lebih melihatnya sebagai perayaan, terutama terkait konsumsi alkohol dan ritual. Kesimpulan: Gawai Dayak memiliki makna yang berbeda di setiap generasi. Para pemimpin adat menekankan aspek spiritualnya, sementara generasi muda berfokus pada sifat perayaannya. Temuan ini menyoroti perlunya transmisi nilai-nilai budaya antargenerasi. Penelitian ini menunjukkan pentingnya melestarikan nilai-nilai tradisional dalam masyarakat. Kata kunci: Gawai dayak; identitas budaya; persepsi antargenerasi; pelestarian budaya; modernitas dan tradisi.